Exome Sequencing Discloses Ionizing-radiation-induced DNA Variants in the Genome of Human Gingiva Fibroblasts. Issue 1 (July 2018) - Nath, Neetika; Esche, Jennifer; Müller, Jessica; Jensen, Lars R.; Port, Matthias; Stanke, Mario; Kaderali, Lars; Scherthan, Harry; Kuss, Andreas W.
Abstract : Abstract: Ionizing radiation can induce genomic lesions such as DNA double-strand breaks whose incomplete or faulty repair can result in mutations, which in turn can influence cellular functions and alter the fate of affected cells and organ systems. Ionizing-radiation-induced sequence alterations/mutations occur in a stochastic manner, which contributes to an increased cancer risk in irradiated individuals. Ionizing radiation exposure, and particularly acute doses at high dose rates (as often observed in radiation accidents), induce alterations in the genome that in part will reflect specific characteristics of the DNA damage response and the repair mechanisms involved. Here, the exome of primary human gingival fibroblasts not exposed or exposed to 0.2, 2, 5, or 10 Gy of x rays was investigated after 16 h of DNA repair for ionizing-radiation-induced mutations. The irradiation effect with varying dose was investigated using three different bioinformatic filters for the analysis of accumulated variants per Mb of genomic DNA and per cytogenetic bands. A highly stringent cutoff of 20‐fold coverage was used for all analyses. Comparing exome DNA from irradiated and nonirradiated cells disclosed a characteristic variation of the frequency of ionizing-radiation-induced single-nucleotide variants as well as small insertions and deletions among chromosomes and their subregions. Increases in ionizing-radiation-induced variants with increasing dose were highly significant ( p = 2.2 × 10 −16, Kruskal-Wallis test). These results indicate that certain chromosomal regions may be more prone to accumulating particular ionizing-radiation-induced alterations than others, which points to a characteristic metasignature in the irradiated exome. Abstract : Supplemental digital content is available in the text.